Underwater Endoscopic Mucosal Resection without Submucosal Injection Facilitates En bloc Resection of Colon Adenomas Extending into a Diverticulum - Yoshikazu Hayashi (Clinical Endoscopy, 2021)
Superficial colonic neoplasms sometimes extend into a diverticulum. Conventional endoscopic mucosal resection of these lesions is considered challenging because colonic diverticula do not have a muscularis propria and are deeply inverted. Even if the solution is carefully injected below the mucosa at the bottom of the diverticulum, the mucosa is rarely elevated from the diverticular orifice, and it is usually just narrowed. Although endoscopic submucosal dissection or full-thickness resection with an over-the-scope clip device enables the complete resection of these lesions, it is still challenging, time consuming and expensive. Underwater endoscopic mucosal resection without submucosal injection (UEMR) is an innovative technique enabling en bloc resection of superficial colon lesions. We report three patients with colon adenomas extending into a diverticulum treated with successful UEMR. UEMR enabled rapid and safe en bloc resection of colon lesions extending into a diverticulum.